2016
DOI: 10.1080/19420862.2016.1267090
|View full text |Cite
|
Sign up to set email alerts
|

Purification of common light chain IgG-like bispecific antibodies using highly linear pH gradients

Abstract: Monovalent bispecific antibodies (BsAbs) are projected to have broad clinical applications due to their ability to bind two different targets simultaneously. Although they can be produced using recombinant technologies, the correct pairing of heavy and light chains is a significant manufacturing problem. Various approaches exploit mutations or linkers to favor the formation of the desired BsAb, but a format using a single common light chain has the advantage that no other modification to the antibody is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…BsAbs are complex molecules and their large scale production has been, and remains, far more challenging than standard monoclonal antibodies. In particular, removal of product-related impurities (or by-products) can be difficult [9,17]. We have shown that tuning the expression of one polypeptide enabled the identification of stable transfected CHO cells not only secreting bsAb titers of more than 1 g/L in shake flasks, but also having an unbalanced content of monospecific by-products that can simplify their elimination during downstream processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BsAbs are complex molecules and their large scale production has been, and remains, far more challenging than standard monoclonal antibodies. In particular, removal of product-related impurities (or by-products) can be difficult [9,17]. We have shown that tuning the expression of one polypeptide enabled the identification of stable transfected CHO cells not only secreting bsAb titers of more than 1 g/L in shake flasks, but also having an unbalanced content of monospecific by-products that can simplify their elimination during downstream processing.…”
Section: Discussionmentioning
confidence: 99%
“…When a bsAb format requires co-expression of three or four polypeptides, by-products resulting from incorrect chain pairing are produced, regardless of the format and engineering approach. Although these by-products may be considered as minor contaminants, it can be challenging to remove them during downstream processing [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Another “two-halves” IgG-like format frequently utilized in contemporary clinical trials are bispecific antibodies with common light chains (CLC, Figure 1 c, Table 1 ), which, like TrioMabs, require multiple purification steps in order to isolate the desired bispecific antibody from the 2 contaminating monospecific antibodies [ 98 ]. Navicixizumab (OMP-305B83) which targets the Notch/Delta-like ligand 4 (DLL4) and the vascular endothelial growth factor (VEGF), showed a disease control rate (DCR) of 32% as monotherapy in a phase 1a trial (NCT02298387) of various solid tumors, and the phase 1b results in combination with chemotherapy are pending (NCT03030287) [ 99 , 100 ].…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…Besides size-based techniques which provide separation based on the hydrodynamic radius, many of the currently reported protocols are performed in the bind and elute mode, where the target molecule bound on the stationary phase is eluted via alterations often in the pH or salt concentration (Chen and Zhang 2021;Li et al 2020). Charge-based purification is frequently employed in the form of ion exchange chromatography (Andrade et al 2019;Jakobsen 2011;Vallera and Miller 2017;Guo et al 2020;Allan et al 2014;Brischwein et al 2006;Kimerer et al 2019;Sharkey…”
Section: Introductionmentioning
confidence: 99%